Behind the mule : race and class in African-American politics - Dawson, Michael C., 1951- (Princeton University Press, 1994)
Political scientists and social choice theorists often assume that economic diversification within a group produces divergent political beliefs and behaviors. Michael Dawson demonstrates, however, that the growth of a black middle class has left race as the dominant influence on African- American politics. Why have African Americans remained so united in most of their political attitudes? To account for this phenomenon, Dawson develops a new theory of group interests that emphasizes perceptions of "linked fates" and black economic subordination.--